Značilnosti kontinuirno ulitih kompozitov Al/SiC - Šuštaršič, Borivoj (Kovine zlitine tehnologije, 1998)
Continuously and discontinuously reinforced Al/SiC metal matrix composites (MMCs) are promising modern, light weight materials with excellent properties,such as: high hardness and strength, good wear resistance, use at elevated temperatures and high modulus of elasticity. Currently, the use of MMCs is limited predominantly on the military and the aerospace industry. However, the penetration of these materials has already begun also in civilian applications. There are several ways of manufacturing of discontinuously reinforced (DR) Al/Sic MMCs: direct incorporation of the reinforcement (SiC particles, platelets or whiskers) into the molten Al alloy,infiltration of SiC preforms with molten Al alloy or via powder metalurgy (PM) procedures. The most promising and probably the cheapest industrial manufacturing procedure of DR Al/SiC MMCs is a direct incorporation of SiC particles into the molten Al alloy during direct vertical continuous (D.C.) casting of billets/ingots. The procedure is already developed on the industrial scale, however, the use, as well as properties of cast composite mportant for further forming to near net shape product (for example with pressure die casting or by hot extrusion) are still rather unknown. Therefore, Duralcan´s D.C. cast composite F3S.20S (Al-9% Si alloy with 20 vol. % of SiC particles) was purchased and analysed. In this article, microstructural and mechanical characteristics of cast composite are present and discussed.
Keywords: kompoziti; aluminijeve zlitine; aluminium alloy; aluminum; aluminij; Aluminij Mostar; silicijev karbid; mikrostruktura; mehanske lastnosti